Estimation based on acceleration measures of an active suspension plant - García Guzmán, Sara Daniela (2015)
The vehicle suspension system is responsible for comfort, safety and vehicle control. In order to positively manipulate these properties, control and estimation theory are used to adapt the system to different road conditions. This paper considers three estimation methods, which are designed to retrieve the system states using only acceleration measures: the Kalman Filter, Particle Filter and Artificial Neuronal Network. Also it considers three control methods: LQR and pole location which it minimizes, the chassis acceleration (a variable used to improve the vehicle comfort). Finally the controllers and estimators are implemented in simulation and in the real plant, using the model of the Quanser active suspension plant.